Gold Nanoparticles (Aunps)-Based Biosensors for Cancer Detection - Gao, Chuxian; Jiang, Zhizhou (Transactions on Materials, Biotechnology and Life Sciences, 2024)
Gold nanomaterials have shown unique advantages in constructing biosensors due to their special optical and electrochemical properties, and have been widely used. This paper investigates improved gold nanoparticles (AuNPs) applications in biosensors for early cancer detection, focusing on the use of AuNPs to improve diagnostic sensitivity and specificity. The introduction emphasizes the critical need for precise early detection technology that can improve cancer treatment outcomes. It describes several biosensing technologies, including aptasensors and microcantilever sensors, where they use AuNPs to improve cancer biomarker detection at low concentrations. Techniques like the green-synthesized AuNPs-based optical fiber ball resonator biosensor are praised for their biocompatibility and environmental benefits, as well as their superior diagnostic performance. Surface-enhanced Raman scattering (SERS) biosensors are also reviewed, demonstrating their capability for high-resolution, multiplexed imaging of cancer cells. This work emphasizes gold nanoparticles' great potential for transforming cancer diagnostics by improving the early detection capabilities of biosensors, which is critical for effective cancer management and therapy.